SPECIFIC INTERNAL FACTORS OF THE FOREIGN POLICY MAKING IN RUSSIA - Puzyrev, Kirill; Druláková, Radka, 1973-; Cibulková, Petra, 1977-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2012)
After the collapse of the Soviet Union and the failure of an ideology of Socialism Russia appeared on a new stage of its development. The political system, its institutions and mechanisms were changed considerably. In this new system appeared new economic, political, social and other factors, conditions and processes which contribute to the formation of the foreign policy of Russia. Thus the research is dealing with such an important component of the foreign policy formation as specific factors and processes occurring within the state. The aim of the paper is to determine the most significant of those factors, find out the reason of their influence and to reveal their weak and strong positions.
Vedoucí práce: Radka Druláková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses